Dielectric Study of Lithium and Sodium Borophosphate Glasses - Jana Mizerakova; Peter Hockicko; Francisco Munoz (Communications - Scientific letters of the University of Zilina, 2017)
Ionic conductivity and dielectric properties such as dielectric permittivity and loss tangent for the samples of lithium and sodium borophosphate glasses were investigated using the electrical conductivity measurements in the range of frequency from 10 Hz to 2 MHz and various temperatures below Tg. The measured data of ac conductivity were described according Jonscher’s power law and experimental values of imaginary part of electric modulus were fitted by KWW function. From the fitted parameters, the activation energies for conduction and relaxation time were found which characterize the hopping processes and transport mechanism in these ion conducting glasses.